Virome and Blood Meal-Associated Host Responses in Ixodes persulcatus Naturally Fed on Patients - Li, Liang-Jing; Ning, Nian-Zhi; Zheng, Yuan-Chun; Chu, Yan-Li; Cui, Xiao-Ming; Zhang, Ming-Zhu; Guo, Wen-Bin; Wei, Ran; Liu, Hong-Bo; Sun, Yi; Ye, Jin-Ling; Jiang, Bao-Gui; et al. (Frontiers in Microbiology, 2022)
The long-lasting co-evolution of ticks with pathogens results in mutual adaptation. Blood-feeding is one of the critical physiological behaviors that has been associated with the tick microbiome; however, most knowledge was gained through the study of laboratory-reared ticks. Here we detached Ixodes persulcatus ticks at different stages of blood-feeding from human patients, and performed high-throughput transcriptomic analysis on them to identify their virome and genes differentially expressed between flat and fully-fed ticks. We also traced bloodmeal sources of those ticks and identified bats and three other potential mammalian hosts, highlighting the public health significance. We found Jingmen tick virus and 13 putative new viruses belonging to eleven viral families, three of which even exhibited high genetic divergence from viruses previously reported in the same tick species from the same geographic region. Furthermore, differential expression analysis suggested a downregulation of antioxidant genes in the fully-fed I. persulcatus ticks, which might be related to bloodmeal-related redox homeostasis. Our work highlights the significance of active surveillance of tick viromes and suggests a role of reactive oxygen species (ROS) in modulating changes in the microbiome during blood-feeding.